Research of Force Analysis of the Split Sprocket Body - Zhai Hongsheng; Xu Yingjie; Yue Xiuren; Xu Wenbo; Li Zhisheng (Jixie chuandong)
At present, the main structural form of sprocket body generally adopts the integral structure at home and abroad, which is difficult to reverse and maintain. The split sprocket shaft group has great advantages in maintenance cost and convenience compared with the integral sprocket shaft group. According to the classical theoretical mechanics, the force analysis of the split sprocket body with new structure is carried out. It is combined with the results of finite element analysis, and then the calculation method of the split sprocket body connection structure design is obtained. This research provides the research method of force analysis of the split sprocket, which can provide necessary loads and constraints for design calculation and finite element analysis. When the split sprocket body is connected by connecting screws, cylindrical pins are set between the upper and lower sprocket bodies to transmit torque, which can ensure the connection reliability of the scraper sprocket of the existing high-power heavy scraper under the conditions of limited installation space and limited number of connecting bolts. Thus it can provide reference and theoretical guidance for the design of similar sprocket bodies in the future.